Pengaruh Word Of Mouth Terhadap Keputusan Pembelian Baso Aci Akang Citra Raya Tangerang - Dini Anindya Julianti; Ahmad Junaidi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2020)
In a business competition that is more competitive. Of course a company must have a promotion which is effective for the company. And then, for an effective promotion you need to consider a product. So, one of the effective marketing is a promotion which is called